Type VI secretion system-associated FHA domain protein TagH regulates the hemolytic activity and virulence of Vibrio cholerae - Guangli Wang; Chan Fan; Hui Wang; Chengyi Jia; Xiaoting Li; Jianru Yang; Tao Zhang; Song Gao; Xun Min; Jian Huang (Gut Microbes)
The type VI secretion system (T6SS) and hemolysin HlyA are important virulence factors in Vibrio cholerae. The forkhead-associated (FHA) domain is a conserved phosphopeptide binding domain that exists in many regulatory modules. The FHA domain protein-encoding gene is conserved in the T6SS gene cluster and regulates the assembly and secretion of the T6SS. This study shows for the first time that the FHA domain protein TagH plays a role in controlling the hemolytic activity of V. cholerae, in addition to regulating the T6SS. TagH negatively regulates HlyA expression at the transcriptional and post-translational levels. The phosphopeptide binding sites of the FHA domain of TagH play a key role in the regulation of hemolytic activity. The deletion of tagH enhances the intestinal pathogenicity and extraintestinal invasion ability of V. cholerae, which mainly depend on the expression of HlyA. This study provides evidence that helps unravel the novel regulatory role of TagH in HlyA and provides critical insights which will aid in the development of strategies to manage HlyA.